Performance Evaluation of a Cowrie-Based Honeypot Integrated with a Suricata Intrusion Prevention System in a School Wireless Network - Putri, Aurellia Maharani; Tahir, Muhlis (Journal of Embedded Systems, Security and Intelligent Systems, 2026)
Purpose – This study aims to implement and evaluate the integration of the Cowrie honeypot model with a Suricata-based Intrusion Prevention System (IPS) as a proactive security solution for school wireless networks. Design/methods/approach – The research method includes a literature review, needs analysis, security topology design, system implementation, and testing using port scanning and SSH brute force attack scenarios. The Cowrie honeypot is utilized to detect and log attack activities, while Suricata functions as an IPS to perform automatic real-time blocking. Findings – The results show that without a security system, both detection and blocking rates were 0%. After implementing Cowrie, the detection rate increased to 100%, although no blocking capability was present. The integration of Cowrie and Suricata IPS achieved 100% detection and 100% blocking rates for port scanning attacks (10 test packets) with an average response time of 0.8 seconds. In the SSH brute force test, the system successfully blocked attacks after 5 out of 10 login attempts, with an average response time of 0.9 seconds. Research implications/limitations – The evaluation was conducted under controlled experimental conditions using a limited number of attack simulations (10 scanning packets and 10 brute force attempts). Therefore, the results may not fully represent performance in large-scale or real-world network environments. Future studies should involve more extensive testing with diverse attack patterns and higher traffic volumes. Originality/value – This study contributes a practical integration of honeypot and IPS technologies to enhance wireless network security in school environments, providing a proactive and automated approach to both detect and mitigate cyberattacks in real time.